Kinerja Katalis Nikel/Titanium Oksida Yang Dibuat Dengan Metoda Impregnasi Terhadap Hidrogenesi Minyak Sawit - Dewi Sondari; S.R Wahuningsih (Research Center for Chemistry - LIPI, 1999)
The preparation of nikel aktif metal catalyst and oksida titanium as supporting materials by impregnation method.The content of metal is various between 20-30% (weight). Specifik surface area of catalyst is measured BET method, the content 22.5% of catalyst have maximal specific surface area is 14,5288m2/gr.From XRD analysis, aktif metal catalyst before reduction is metal oksida NiO (200) at 20 = 43,47, after reduction showednickle metal cristal at 20 = 44,50 is peak caracteristic from Ni (111).Test activity comerical catalyst after reaction time two hoursiodine number decreased 34,00 preparated catalyst 44,50 atcontent 22,5%.